Stability of nucleic acid base pairs in organic solvents: molecular dynamics, molecular dynamics/quenching, and correlated ab initio study - Zendlová, Lucie; Hobza, Pavel; Kabeláč, Martin (The journal of physical chemistry. B, 2007)
The dynamic structure and potential energy surface of adenine...thymine and guanine...cytosine base pairs and their methylated analogues interacting with a small number (from 1 to 16 molecules) of organic solvents (methanol, dimethylsulfoxide, and chloroform) were investigated by various theoretical approaches starting from simple empirical methods employing the Cornell et al. force field to highly accurate ab initio quantum chemical calculations (MP2 and particularly CCSD(T) methods). After the simple molecular dynamics simulation, the molecular dynamics in combination with quenching technique was also used. The molecular dynamics simulations presented here have confirmed previous experimental and theoretical results from the bulk solvents showing that, whereas in chloroform the base pairs create hydrogen-bonded structures, in methanol, stacked structures are preferred. While methanol (like water) can stabilize the stacked structures of the base pairs by a higher number of hydrogen bonds than is possible in hydrogen-bonded pairs, the chloroform molecule lacks such a property, and the hydrogen-bonded structures are preferred in this solvent. The large volume of the dimethylsulfoxide molecule is an obstacle for the creation of very stable hydrogen-bonded and stacked systems, and a preference for T-shaped structures, especially for complexes of methylated adenine...thymine base pairs, was observed. These results provide clear evidence that the preference of either the stacked or the hydrogen-bonded structures of the base pairs in the solvent is not determined only by bulk properties or the solvent polarity but rather by specific interactions of the base pair with a small number of the solvent molecules. These conclusions obtained at the empirical level were verified also by high-level ab initio correlated calculations.
Keywords: zastoupení bazí; Water; Nucleic Acid Conformation; Base Pairing; Financing, Organized; financování organizované; Chloroform; dimethylsulfoxid; voda; Computer Simulation; vodíková vazba; nukleotidy; Dimethyl Sulfoxide; Hydrogen Bonding; konformace nukleové kyseliny; Base Composition; počítačová simulace; Nucleotides; methanol; chloroform; molekulární modely; párování bází; DNA Methylation; metylace DNA; Models, Molecular; Methanol